Looking for the missing rich: tracing the top tail of the wealth distribution - Stefan Bach; Andreas Thiemann; Aline Zucco (International Tax and Public Finance, 2019)
We analyse the top tail of the wealth distribution in France, Germany, and Spain using the first and second waves of the Household Finance and Consumption Survey (HFCS). Since top wealth is likely to be under-represented in household surveys, we integrate big fortunes from rich lists, estimate a Pareto distribution, and impute the missing rich. In addition to the Forbes list, we rely on national rich lists since they represent a broader base of the big fortunes in those countries. As a result, the top 1% wealth share increases notably for the three selected countries after imputing the top wealth. We find that national rich lists can improve the estimation of the Pareto coefficient in particular when the list of national USD billionaires is short.
Keywords: D31; C46; C81; 330; Wealth distribution; Missing rich; Pareto distribution; HFCS